The Mediating Role of Innovation Performance between the Relationship of Green Supply Chain Management Skills and Environmental Performance - Kittisak Jermsittiparsert; Jutamat Sutduean; Chutipan Sutduean (International Journal of Supply Chain Management, 2019)
Current study examines the effect of Green Supply Chain Management (GSCM) skills on the environmental performance of manufacturing companies in Thailand. This study also evaluate the mediating role of innovation performance among the relationship of GSCM skills and environmental performance. The sample was limited to the firms that had certification of ISO 14001 EMS in Thailand. Data were collected from the companies mentioned above through a questionnaire. The technique that is used to investigate the association between the understudy variables is PLS-SEM. Multiple regression has been used to test the direct relationship among the variables used in the study while multiple regression with the bootstrapping procedure is used to check the mediating role of innovation performance on the association of GSCM skills and environmental performance. The results revealed a positive association between GSCM skills and environmental performance. In addition, results also elaborated that innovation performance mediates the association between GSCM skills and firm’s environmental performance.